Особенности изменения гематологических показателей полевки-экономки и закаспийской полевки. Сообщение I - Рогатко, И.В. (Вестник зоологии, 1976)
The peculiarities of individual variability are considered for some hematological indexes of two species of voles (age and seasonal). High hematological characteristics are observed as in other micromammals.